2007
DOI: 10.1016/j.beproc.2006.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Timing of omitted events: An analysis of temporal control of inhibitory behavior

Abstract: This paper reviews research designed to investigate the temporal control of inhibitory responding using rats as subjects. One area of investigation has focused on the role of temporal variables in conditioned inhibition produced using Pavlov's (1927) procedure. These studies have found that evidence of conditioned inhibition obtained by negative summation testing is strongest when the conditioned inhibitor signals the omission of the US at the same temporal location as a transfer excitor signals presentation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Conditioned inhibition poses higher technical challenges for a model of learning and timing as responses cannot be directly observed. To assess conditioned inhibition two types of measures are used (Denniston and Miller, 2007): summation and retardation tests. There are different procedures that can generate inhibition, so we refer here specifically to the inhibition produced by alternating A+ with AB-trials.…”
Section: Time Specificity Of Conditioned Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conditioned inhibition poses higher technical challenges for a model of learning and timing as responses cannot be directly observed. To assess conditioned inhibition two types of measures are used (Denniston and Miller, 2007): summation and retardation tests. There are different procedures that can generate inhibition, so we refer here specifically to the inhibition produced by alternating A+ with AB-trials.…”
Section: Time Specificity Of Conditioned Inhibitionmentioning
confidence: 99%
“…In retardation tests, the inhibitor by itself is now paired with the US, and it is said to pass the test if acquisition is slower than with a neutral stimulus. Denniston and Miller (2007) reviewed a series of studies that varied the durations of the training excitor and that between the inhibitor and the training excitor. The studies showed that conditioned inhibition is observed when the temporal relations between training and testing are preserved, and not otherwise.…”
Section: Time Specificity Of Conditioned Inhibitionmentioning
confidence: 99%
“…1 Note that there are no inhibitory associations. Behavior indicative of inhibition arises as a result of the relative values of different excitatory associations (see Denniston and Miller, 2007).…”
Section: The Extended Comparator Hypothesismentioning
confidence: 99%
“…Several learning phenomena known from studies on classical conditioning in vertebrates have been demonstrated in honeybees, including trace conditioning (Szyszka et al 2011), backward conditioning (Bitterman et al 1983Hellstern et al 1998;Dacher and Smith 2008;Felsenberg et al 2014a), second-order conditioning (Hussaini et al 2007), extinction learning (Sandoz and Pham-Delegue 2004;Stollhoff et al 2005;Eisenhardt and Menzel 2007;Stollhoff and Eisenhardt 2009;Plath et al 2012), sensory preconditioning (Müller et al 2000, and blocking (Guerrieri et al 2005; for a contrasting review, see Gerber and Ullrich 1999), latent inhibition (Chandra et al 2010), and occasion setting (Mota et al 2011). These phenomena are surprisingly similar to vertebrates, in which they were initially described (Bouton 1993;Fanselow 1998;Schmajuk et al 1998;Myers and Davis 2002;Gewirtz and Davis 2006;Denniston and Miller 2007;Raybuck and Lattal 2014). This suggests that the underlying neuronal mechanisms are also likely based on common principles.…”
mentioning
confidence: 50%